2021
DOI: 10.21323/2414-438x2021-6-1-39-45
|View full text |Cite
|
Sign up to set email alerts
|

A study on the chemical and mineral composition of the protein-mineral paste from poultry and cattle bone raw materials

Abstract: When processing cattle and poultry, a large quantity of secondary slaughter products in the form of bone raw materials are formed in enterprises of the meat and poultry processing industry. Nowadays, its use is not optimal and rational. One of the promising directions of using bone raw materials in enterprises is production of finely ground meat and bone paste. The aim of this research was to study the chemical and mineral compositions, as well as the content of toxic elements in meat and bone paste from poult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Even though chicken is known as a good source of protein, the mineral content in chicken is said to be lower compared to cattle meat. Another research showed that chicken meat contained much lower Calcium (Ca), Magnesium (Mg), and Iron (Fe) [4,28]. Another essential mineral, Zinc (Zn) is also found to be lower in chicken meat.…”
Section: Introductionmentioning
confidence: 99%
“…Even though chicken is known as a good source of protein, the mineral content in chicken is said to be lower compared to cattle meat. Another research showed that chicken meat contained much lower Calcium (Ca), Magnesium (Mg), and Iron (Fe) [4,28]. Another essential mineral, Zinc (Zn) is also found to be lower in chicken meat.…”
Section: Introductionmentioning
confidence: 99%
“…In the processing of poultry, almost 20-25% of the live weight of poultry are called "secondary products" of poultry processing (necks, carcasses, wing tips, backs, legs, breasts, etc. ), as well as meat and bone residues (MBR) of poultry, which have a significant weight among the by-products of poultry processing [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Chicken bone can be used in many ways besides the production of collagen products. The chemical composition of the chicken bone: 15.6% protein, 9.5% fat, 14.7% minerals and 57.5% water [11,12]. The purpose of this work is to study the influence of the fine grinding process on the temperature characteristics and water-binding capacity of meat and bone paste.…”
Section: Introductionmentioning
confidence: 99%